Soldados sin rostro : los servicios de información, espionaje y criptografía en la Guerra Civil Española, 1936-1939 / José Ramón Soler Fuensanta, Francisco Javier López-Brea Espiau - López-Brea Espiau, Francisco Javier; Soler Fuensanta, Josep Ramon (Historia Inédita)
Bibliografía: p. [303]-310